Característica de las economías actuales: el intervencionismo - Rivas Santos, Pablo (2009)
This paper shows that the interventionist economic system is inherent in most of the economies of countries in the world, since the intervention, despite his actions that disrupt the market mechanism does not strive to remove this duality that exists in the market economy the state and market activity. The problem is to determine who will plan and lead. If each person will be in accordance with their value judgments, or be the ruler paternal name of all. The dilemma is choosing between the free and independent act of the person or the submission of the person subject to ap.eal government decisions. It is a choice between freedom and dictatorship. The laissez-faire is intended to make free for all: each will decide how to cooperate in the social division of labor, and who are the consumers who determine what employers have to produce. The planning involves the governor to authorize, for and of itself, protected by the springs of repression, resolve and enforce. All state interference in the market sphere, indirectly impact on consumption. Because altering the market mechanism, government interference and influences the behavior of consumers considered securities. Interventionism always breeds corruption.